Utilization of kangkong (Ipomoea aquatica) leaves in the fortification of crackers. - Zomil, Nica Pearl Solis
Micronutrient deficiency is a widespread health problem in the country and affects all age groups, mostly children. One solution that can combat this sickness is through the fortification of food products with vitamins and minerals. The study used Kangkong powder in fortification of crackers. Three formulation with varying Kangkong concentrations, 5%, 10% and 12%, were made. A preference rank test was conducted to determine the most preferred amomg the panelists. The most preferred among panelists. The most preferred formulation was the crackers that contained 5% Kangkong powder. The sample was subjected to characterization and sensory evaluation. The analyses were done in two runs. The results of the descriptive sensory evaluation test showed that majority of the panelists perceived the crackers as light green in color, have a crunchy texture, have distinct Kangkong flavor but only a slightly distinct Kangkong odor. The proximate composition of the most preferred formulation was determined and mean results of the two runs showed that moisture content of the crackers was 3.69±0.18%, crude ash 1.92±0.08%, crude fat 6.43±2.72%, crude fiber 1.76±0.11%, crude protein 11.97±0.96% and carbohydrates 74.23±1.75%. Water activity of the crackers averaged at 0.275. Micronutrient analysis showed that both the iron (0.0520 mg Fe/ g sample) and β-carotene (1385 μg/100g.) content of the Kangkong crackers increased as compared to the control. The study showed that the addition of Kangkong powder as a fortificant to crackers was able to increase its micronutrient levels. Also, with the consumption of the fortified product, consumers will be provided with a part of their recommended dietary allowance for iron and vitamin A intake.